Emphysematous Pyelonephritis in a 32-Year-Old Diabetic Female (Journal of Enam Medical College, 2015)
Emphysematous pyelonephritis is a rare, severe, necrotizing renal parenchymal infection characterized by gas accumulation in kidney(s) with or without involving surrounding tissues. Patients with diabetes mellitus are the usual sufferers. Here we describe a case history of a young Bangladeshi diabetic lady who presented with dysuria, fever and abdominal pain. Investigations confirmed left sided emphysematous pyelonephritis. She responded to and recovered with intravenous antibiotics.J Enam Med Col 2015; 5(2): 122-124